Direct and post-compressed sound fields for different coded excitations - experimental results - KLIMONDA, Z.; LEWANDOWSKI, M.; NOWICKI, A.; TROTS, I.; LEWIN, P. A. (Archives of Acoustics, 2005)
Coded ultrasonography is intensively studied in many laboratories due to its remarkable properties: increased depth penetration, signal-to-noise ratio (SNR) gain and improved axial resolution. However, no data concerning the spatial behavior of the pressure field generated by coded bursts transmissions were reported so far. Five different excitation schemes were investigated. Flat, circular transducer with 15 mm diameter, 2 MHz center frequency and 50% bandwidth was used. The experimental data was recorded using the PVDF membrane hydrophone and collected with computerized scanning system developed in our laboratory. The results of measured pressure fields before and after compression were then compared to those recorded using standard ultrasonographic short-pulse excitation. The increase in the SNR of the decoded pressure fields is observed. The modification of the spatial pressure field distribution, especially in the intensity and shape of the sidelobes is apparent. Coded sequences are relatively long and, intuitively, the beam shape could be expected to be very similar to the sound field of long-period sine burst. This is true for non-compressed distributions of examined signals. However, as will be shown, the compressed sound fields, especially for the measured binary sequences, are similar rather to field distributions of short, wideband bursts.